Grzeczność językowa korespondencji elektronicznej w nauczaniu języka polskiego jako obcego - Jezierska, Beata; Jakobsze, Małgorzata (Poznańskie Spotkania Językoznawcze, 2014)
The aim of the article has been to bring attention to the instability of the Polish pattern of electronic correspondence by using a distinct comparative background, i.e., the practice of teaching the Polish language to foreigners outside the territory of Poland (in this particular case – the Italians). The efficiency of the modern didactic methods in combination with a high degree of conventionality of the rules of language etiquette are conducive for a quick mastery of correct (expected) linguistic behaviours by the students of the Polish language learning it outside Poland. It turns out, however, that in the Internet reality, the standards of linguistic politeness – generally accepted by a given language community – undergo negative reevaluation due to which the native users of both the Polish language as well as other languages, encounter problems with a dynamic and chaotically changing formula of contacting by means of e-mail.